Salmonella Typhimurium Invalidated for the Three Currently Known Invasion Factors Keeps Its Ability to Invade Several Cell Models - Roche, Sylvie M.; Holbert, Sébastien; Trotereau, Jérôme; Schaeffer, Samantha; Georgeault, Sonia; Virlogeux-Payant, Isabelle; Velge, Philippe (Frontiers in Cellular and Infection Microbiology, 2018)
To establish an infection, Salmonella has to interact with eukaryotic cells. Invasion of non-phagocytic cells (i.e. epithelial, fibroblast and endothelial cells) involves either a trigger or a zipper mechanism mediated by the T3SS-1 or the invasin Rck, respectively. However, unknown invasion factors have been previously suggested. Our goal was to evaluate the invasion capability of a Salmonella Typhimurium strain invalidated for the three known invasion factors. Non-phagocytic cell lines of several animal origins were tested in a gentamicin protection assay. In most cells, we observed a drastic decrease in the invasion rate between the wild-type and the triple mutant. However, in five cell lines, the triple mutant invaded cells at a similarly high level to the wild-type, suggesting the existence of unidentified invasion factors. For both strains, scanning-electron microscopy, confocal imaging and use of biochemical inhibitors confirmed their cellular uptake and showed a zipper-like mechanism of internalization involving both clathrin- and non-clathrin-dependent pathways. Despite a functional T3SS-1, the wild-type bacteria seemed to use the same entry route as the mutant in our cell model. All together, these results demonstrate the existence of unknown Salmonella invasion factors which require further characterization.